Stemming the Diffusion of Responsibility: A Longitudinal Case Study of America's Chemistry Teachers. (November 2014) - Rushton, Gregory T.; Ray, Herman E.; Criswell, Brett A.; Polizzi, Samuel J.; Bearss, Clyde J.; Levelsmier, Nicholas; Chhita, Himanshu; Kirchhoff, Mary
National initiatives to expand the aggregate science, technology, engineering, and math (STEM) workforce reflect America's goals to increase global competitiveness. However, the aggregation of STEM stakeholders may elicit a diffusion of responsibility because individuals assume others are already acting. Here, we perform a longitudinal case study of U.S. public school chemistry teachers to illustrate a diffusion of responsibility within the STEM community regarding who is responsible for the teacher workforce. Utilizing the 1987–2007 Schools and Staffing Survey (SASS) data, we determine how chemistry teacher demographics compare to other disciplines. Our results suggest that the aggregate success of STEM education initiatives may mask the need for discipline-specific reform. We describe reforms in the context of boundary objects and discuss implications for policy decisions as boundary crossings .